PENGARUH ADMINISTRASI KEPENDUDUKAN TERHADAP AKURASI DATA IDENTITAS KEPENDUDUKAN DIGITAL (IKD) PADA KECAMATAN LENGKITI KABUPATEN OGAN KOMERING ULU - Anty Oktavia; Eva Susanti; Aprilia Lestari (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the effect of population administration on the accuracy of Digital Population Identity (Identitas Kependudukan Digital/IKD) data in Lengkiti District, Ogan Komering Ulu Regency. The research employed a quantitative method with a correlational approach. Data were collected through questionnaires distributed to 100 respondents who are users of population administration services and IKD. Data analysis techniques included validity testing, reliability testing, simple linear regression analysis, and hypothesis testing using t-test and F-test. The results indicate that population administration has a positive and significant effect on the accuracy of IKD data, as evidenced by a significance value of less than 0.05, indicating that the research hypothesis is accepted. The coefficient of determination (R²) value of 0.245 shows that population administration contributes 24.5% to the accuracy of IKD data, while the remaining 75.5% is influenced by other factors outside the scope of this study. According to the author, these findings suggest that although population administration has a significant influence, its contribution is still at a moderate level, implying that IKD data accuracy is not solely determined by administrative factors. Other contributing factors include the readiness of human resources, public awareness and understanding, the stability of digital systems, and the effectiveness of data supervision and verification processes. The implementation of orderly, integrated, and digitally based population administration has proven to improve the validity, completeness, and consistency of population data; however, its effectiveness will be more optimal when supported by enhanced staff capacity, improved information technology infrastructure, and continuous public outreach. Therefore, the implementation of IKD should be viewed as a continuous process that requires synergy between systems, administrative personnel, and community participation to achieve accurate, up-to-date, and reliable population data as a foundation for public service delivery.